Association of COVID-19 case fatality rate with disease burden: an ecological analysis in Italy during the first wave. (October 2021) - Timelli, Laura; Liuzzi, Giuseppina; Cannavacciuolo, Alessandro; Petrosillo, Nicola; Puro, Vincenzo; Girardi, Enrico
Highlights: The high burden of COVID-19 may have contributed to an increased disease fatality [Au?3]. The association of the case fatality rate with the cumulative incidence of COVID-19 and other factors was evaluated. The burden of COVID-19 on the health system also needs containment in order to limit mortality. Abstract: Objectives: In Italy, the case fatality rate (CFR) of coronavirus disease 2019 (COVID-19) during the first wave of the pandemic showed significant geographic heterogeneity. The aim of this study was to explore the possible association between the CFR and measures of disease burden in the Italian regions using an ecological approach. Methods: Cumulated regional data for the period February 24 to May 11, 2020 were analysed to assess the association of the CFR with the cumulative incidence of COVID-19 and the ratio between the maximum number of COVID-19 patients in intensive care units (ICU) and ICU beds available before the pandemic (ICU load), adjusting for median age of the patients at disease onset, number of nasopharyngeal swabs performed per confirmed case, and prevalence of chronic diseases . Results: During the study period, the COVID-19 CFR in the Italian regions ranged between 5.0% and 18.4%. On multivariable regression analysis, the CFR was found to be significantly associated with the cumulative incidence (relative rate (RR) 1.02 per 100 cases/1 million increase), median patient age (RR 1.07 per 1 year increase), and ICU load (RR 1.72, 2.18, and 2.57, for >40–70% vs ≤40%, 70–140% vs ≤40%, and ≥140 vs ≤40%, respectively). Conclusions: A high burden of COVID-19 may contribute to increased disease fatality, possibly as a result of the increasing demand for care of critically ill patients beyond health system capability.